Haters Phenomena in Social Media - Angga Pradipta; Nuriyatul Lailiyah, S.Sos, M.I.Kom (Interaksi Online, 2016)
Social media is internet-basic media, functioned as interaction media room based on multimedia technology. And social media created some effects. One of the negative effects of social media is haters phenomena. Haters are a person who easily said dirty words, harass, and humiliate to others. This phenomena causes anxiety—especially in Indonesia, even the Government issued public policy and letter of regulation about this phenomena, through Paragraph 27 verse (3) IT Constitution, Paragraph 45 verse (1) IT Constitution and Kapolri Letter SE/6/X/2015. Haters phenomena increasingly uncontrolled even many public figure affected by this phenomena. Goals of this research are to understand the impact of social media for haters phenomena and to understand haters attitude in social media and in their real life. Methodology of this research is combination of quantitative and qualitative method with case study approach. The theories are Social Media Effect, Verbal Aggressive, and Impression Management. The result of this research shows: (1) High frequencies of social media usage make haters feel addict. (2) Someone who online more than other, tend to open their selves easily. (3) The haters think if verbal aggressive that they do is positive way to criticize something. (4) The haters’ attitude in social media and in their real life is similar. (5) Characteristics of verbal aggressive are shown by all haters. (6) The haters think that their attitudes in social media are the way to show their positive-face to the public. Whereas their attitudes are tend to aggressive communication. The conclusions of this research are social media cause addiction effect that construct haters’ mind and attitude. What they already show to us through social media is their real-life attitude. Aggressive communication is a form to criticize something as their effort to show their positive-face. The suggestion are, surveillance to social media usage, activate the regulations for haters’ phenomena, and socialization the effect of social media in the schools.